A Dosimetry Study of Portable X-ray Fluorescence in Vivo Metal Measurements. Issue 5 (May 2019) - Specht, Aaron J.; Zhang, Xinxin; Goodman, Benjamin D.; Maher, Ed; Weisskopf, Marc G.; Nie, Linda H.
Abstract : Abstract: Portable x-ray fluorescence devices have grown in popularity for possible metal exposure assessment using in vivo measurements of bone and toenail. These measurements are accompanied by a small radiation dose, which is typically assessed by radiation safety committees to be minimal. However, an understanding of precise dose under different instrument conditions is still needed. This study set out to do a thorough investigation of the exact dose measurements using optically stimulated dosimeters, thermoluminescent dosimeters, and simulation with a Monte Carlo N-Particle transport code to assess the skin and total-body effective dose typical of portable x-ray fluorescence devices. We showed normal linear relationships between measurement time, x-ray tube current, and radiation dose with the device, and we showed a second order polynomial relationship with increasing voltage and radiation dose. Dose was quantified using thermoluminescent dosimeters, optically stimulated dosimeters, and simulations, which gave similar dose estimations. Skin dose for a standard 50-kV, 40-μA measurement for bone and toenail in vivo was 48.5 and 28.7 mSv, respectively, according to simulation results. Total-body effective dose was shown as 3.4 and 2.0 μSv for in vivo bone and toenail measurements, respectively, for adults using the portable x-ray fluorescence device.